Ketidakadilan Gender Dalam Kumpulan Cerpen Saia Karya Djenar Maesa Ayu: Tinjauan Sastra Feminis Dan Implementasinya Sebagai Bahan Ajar Sastra di SMA - Kartika Ayu Ningrum, Eva (2016)
xii GENDER INJUSTICE IN SHORT STORY COLLECTION 'SAIA' WRITTEN BY DJENAR MAESA AYU: A FEMINIST LITERARY APPROACH AND ITS IMPLEMENTATION AS A LITERARY TEACHING MATERIAL IN SENIOR HIGH SCHOOL Eva Kartika Ayu Ningrum, A 310110139, Indonesian Education, Teacher Training and Education Faculty, Muhammadiyah University of Surakarta, 2016, 128 pages, evakartikaayu18@gmail.com. Abstract This research aimed at (1) explaining the social-historical background of Djenar Maesa Ayu as the writer of short story collection 'Saia', (2) explaining the structure of short story collection 'Saia' written by Djenar Maesa Ayu, (3) elaborating the gender injustice in the short story collection 'Saia' written by Djenar Maesa Ayu, and (4) explaining the results of the implementation of gender injustice analysis in the short story collection 'Saia' viewed from feminist literarature as a literary teaching material in Senior High School. This research was a descriptive qualitative research with the research object was gender injustice in the short story collection 'Saia'. Data in this research were paragraphs describing the structure, gender injustice, and curriculum related to the short story. The data source was the short story collection 'Saia' written by Djenar Maesa Ayu. The techniques of data collection used were library technique, observing and taking a note. The data analyzed were thee short stories full of gender injustice, they were: Air, Sementara, and Mata Telanjang. The results of the research were elaborated as follows: (1) The social-historical background of the writer (Djenar Maesa Ayu) is a writer who always raises problems on women, therefore it influences her works. (2) The structures of the three short stories had themes about a woman' struggle, free-sex, the life of a striptease dancer in a night club, the plots of the three short stories are chronological plot and have setting of time of 2000s. (3) This research had four gender injustice divided into: woman subordination, woman stereotype, violence on woman, and work load. (4) The short story collection 'Saia' could not be used as a literary teaching material in the learning of Indonesian in Senior High School class X1 semester 1 because it was not appropriate to the criteria of teaching material suitability that includes language aspect, psychology, and social-cultural background.